Ultra-purification of Lipopolysaccharides reveals species-specific signalling bias of TLR4: importance in macrophage function - Matthew Stephens (Nature Portfolio, 2021)
Abstract TLR4 location, and bacterial species-derived lipopolysaccharides, play a significant role in the downstream activation of transcription factors, accessory molecules, and products. Here, this is demonstrated through the use of classically-activated and alternatively-activated macrophages. We show that, when polarized, human macrophages differentially express and localize TLR4, resulting in biased recognition and subsequent signalling of LPS derived from Pseudomonas aeruginosa, Escherichia coli, and Salmonella enterica. Analysis of activation demonstrated that in classically activated macrophages, P. aeruginosa signals from the plasma membrane via TLR4 to p65 dependent on TAK1 and TBK1 signalling. E. coli signals dependent or independent of the endosome, utilizing both TAK1- and TBK1-signalling to induce P65 and IRF3 inducible genes and cytokines. S. enterica however, only induces P65 and IRF3 phosphorylation through signalling via the endosome. This finding outlines clear signalling mechanisms by which innate immune cells, such as macrophages, can distinguish between bacterial species and initiate specialized responses through TLR4.